THE RELATIONSHIP OF THE LEVEL OF MALOCLUSION SEVERITY BASED ON THE ICON (INDEX OF COMPLEXITY, OUTCOME AND NEED) WITH THE RISK OF CARIES JUDGED FROM THE PLAQUE ATTACHMENT IN ADOLESCENTS AT TABANAN - Hutomo, Louise Cinthia; Anggraini, Ni Luh Putu Mira (E-Jurnal Medika Udayana, 2024)
Malocclusion is a frequent problem that can be found at the oral and dental health care. Individual’s abnormal teeth condition with malocclusion can become a risk to caries, this condition happen because of difficulty to clean teeth mechanically when brushing teeth. This study trying to find the correlation between orthodontic treatment need with risk of caries. This research is an analytical observational research with a cross sectional study design. The sampling process was done by using multistage random sampling which taken from seventh, eighth, and ninth class of the SMP N 2 Marga (Junior High School). Total number of samples are 90 people with same distribution for each class. Orthodontic treatment need can be measured by ICON (Index of Complexity, Outcome and Need) and risk of caries can be determined by GC Tri Plaque ID Gel that applied for all samples. Statistic hypothesis of this study tested using non parametric test such as Spearman Rank Correlation. The results showed that samples that did not need orthodontic treatment experienced low caries risk (36%), moderate caries risk (13%) and high caries risk (0%). Samples that included borderline cases experienced low caries risk (11%), moderate caries risk (15%) and high caries risk (0%). Samples requiring orthodontic treatment experience low caries risk (1%), moderate caries risk (10%) and high caries risk (4%). Statistical analysis showed correlation coefficient of 0.585, there was a relationship between the orthodontic treatment need with caries risk, with a value p = 0,000 which means there is a significant relationship between orthodontic treatment need with the risk of caries . Keywords : Malocclusion, ICON, Caries Risk